Evidence of major secondary organic aerosol contribution to lensing effect black carbon absorption enhancement. Issue 1 (December 2018) - Zhang, Yunjiang; Favez, Olivier; Canonaco, Francesco; Liu, Dantong; Močnik, Griša; Amodeo, Tanguy; Sciare, Jean; Prévôt, André; Gros, Valérie; Albinet, Alexandre
Abstract Atmospheric black carbon (BC) has a strong positive, but still controversial, effect on global warming. In particular, BC absorption enhancement (E abs ) due to internal mixing with other chemical species—so-called lensing effect—is poorly assessed. This bottleneck partly relies on the lack of long-term in situ measurements of both the optical and chemical properties of BC-containing particles. Here, we present experimental and computational results showing a significantE abs increase with the aerosol photochemical aging. This was associated with the production of highly oxidized secondary organic aerosols (SOA), especially at summertime. The 3-year-long continuous aerosol chemical and optical measurements used for the present study was obtained in the Paris region, France, which might be representative of near-future air quality within developing countries. These findings suggest that SOA could represent one of the most critical chemical species to be considered within climate models. Atmospheric chemistry: organic aerosols amplify atmospheric warming from black carbon Tiny remnants of combustion, known as black carbon, absorb solar radiation and warm the atmosphere—an effect that can be doubled by "lensing" from secondary organic aerosols. A multi-institution team led by Olivier Favez at the Institut National de l'Environnement Industriel et des Risques conducted a three-year observational and modeling study near Paris. The researchers tested a range of atmospheric constituents and found that secondary organic aerosols—adhered to black carbon particles—are the most important determinant of the enhanced warming. The aerosols are produced by photochemical reactions with a wide variety of natural and human-produced volatile organic compounds, and act to focus solar radiation to the core of the black carbon particle, especially during the particle aging process during summer. The findings—although specific to Paris—provide insights into the specific compounds leading to enhanced warming, and reveal the most effective targets for remediating their effect.